The use of the wetting front detector as an irrigation-scheduling tool for pepper production in the upper east region of Ghana: evidence from field experiment and farmers' perceptions - Adimassu, Zenebe; Balana, Bedru; Appoh, Richard K.; Nartey, Eric Gbenatey (Wiley, 2020)
We compare the effect of the wetting front detector on yield and water productivity with farmers' practices (FP) and irrigation requirements based on crop water requirement calculation (IRCWR). A field experiment was conducted to assess the effect of the wetting front detector, FP and IRCWR combined with six fertilizer rates. We also interviewed 50 farmers to understand their perception about the use and associated concerns with the wetting front detector. Analysis of variance and partial budget economic analysis were performed. The results show that the wetting front detector saved 16% of irrigation water compared to FP, which in turn led to 16% labour saving to irrigate pepper as compared to FP. Yield and water productivity of pepper were not significantly affected by the irrigation regimes. Regardless of irrigation regimes, yield of pepper was significantly influenced by fertilizer treatment in both years. Although the highest fresh fruit yield of pepper (8.6 t ha-1 ) was recorded from Fortifer granules, the highest marginal rate of return was obtained from application of inorganic fertilizer including 173 N, 36 P,18 K ha ¹. The majority of farmers perceived the wetting front detector as low risk and compatible to use. The result also suggests that farmers are interested in buying and adopting the tool for future use.